PROBLEMATIKA ASTROFOTOGRAFI DALAM RUKYATUL HILAL - Hastuti; Basithussyarop, M. Basithussyarop (ELFALAKY: Jurnal Ilmu Falak, 2022)
In determining the beginning of the month of Qamariyah with the Rukyatul Hilal method, it cannot be separated from astrophotography techniques which aim to photograph celestial bodies, especially perpetuating the process of observing the new moon in the form of images or images that can be used as new moon data in a scientific development related to the new moon. Where the new moon in determining the beginning of the month is a dim and very thin object, while the witness sees it as the basis for determining the beginning of the month. Although the existence of the crescent moon in the process of processing the new moon cannot be ascertained, processing the image is able to clarify the image of the crescent moon to be more alive by following developments in optical and digital technology as one of the offers that can be used to increase objectivity in rukyatul hilal. Keywords: Rukyatul Hilal, Astrophotography, Ulama's .